Proposed Business Models and Parameters in Over-The-Top Initiatives - Confido, Jemy Vestius; Wibison, Dermawan; Sunitiyoso, Yos (International Journal of Engineering and Technology, 2018)
Communication service providers (CSPs) are confronting challenges from the over-the-top (OTT) players that have been providing free-like services using various indirect-charging business models in addition to the network infrastructure developed by the CSPs. To encounter the challenges, CSPs should embrace OTT opportunities, deploy the right business models and set relevant business parameters accordingly. After conducting action research (AR) at one of Asia Pacific’s largest CSPs, this research identifies five business models, including three indirect-charging models and four business parameters that can determine the efficacy of an applied OTT business model. The research also finds that the business models can be mixed as similarly the business parameters can be combined according to the business model. Finally, the research concludes that the presence of OTT business model mix table and OTT business model canvass are very helpful for the business managers when developing OTT initiatives.